2022
DOI: 10.1186/s12875-022-01751-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to following imaging guidelines for the treatment and management of patients with low-back pain in primary care: a qualitative assessment guided by the Theoretical Domains Framework

Abstract: Background Low back pain (LBP) is a leading cause of disability and is among the top five reasons that patients visit their family doctors. Over-imaging for non-specific low back pain remains a problem in primary care. To inform a larger study to develop and evaluate a theory-based intervention to reduce inappropriate imaging, we completed an assessment of the barriers and facilitators to reducing unnecessary imaging for NSLBP among family doctors in Newfoundland and Labrador (NL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“… 38 Recent work has identified that fear of negative consequences, low counseling time, and lack of access to appropriate practitioners act as barriers to following evidence-based imaging guidelines in primary care physicians treating LBP. 39 Built into our model is access to health coaching, physical therapy, and other ancillary needs which may be helpful to provide care, potentially lessening the impetus for imaging.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Recent work has identified that fear of negative consequences, low counseling time, and lack of access to appropriate practitioners act as barriers to following evidence-based imaging guidelines in primary care physicians treating LBP. 39 Built into our model is access to health coaching, physical therapy, and other ancillary needs which may be helpful to provide care, potentially lessening the impetus for imaging.…”
Section: Discussionmentioning
confidence: 99%
“…One coder (DT) identified the domains representing key barriers and enablers to enhancing fidelity to provider training or intervention delivery of the proposed intervention. The domains most likely representing perceived barriers and enablers were identified through considering the frequency of the belief statements, the presence of conflicting beliefs (i.e., participants reporting mixed views for a particular strategy to enhance fidelity to provider training or intervention delivery), and the perceived strength of the impact a belief may have on enhancing fidelity to provider training and intervention delivery (i.e., participants expressing beliefs they were particularly vocal about determined by length of participant quote or the use of emphatic or emotional speech) [ 31 , 32 ]. Using these criteria, the research team decided to take a more conservative approach to considering domains as non-relevant.…”
Section: Methodsmentioning
confidence: 99%
“…External drivers: (dis)incentives (Bussières et al, 2012;Pike et al, 2022), referral requirements (Nevedal et al, 2020;Pike et al, 2022), insurance/compensation claims (Blokzijl et al, 2021;Pike et al, 2022), surgical candidacy, colleague requests (Pike et al, 2022). Behavioural regulators: Access to other clinicians, patient education material, decision support tools (Pike et al, 2022), previous imaging . Knowledge (Un)familiarity/(un)awareness of CPG's (Bussières et al, 2012;Ganesh et al, 2022;Nevedal et al, 2020;Pike et al, 2022;, (dis)agreement with CPG (Bussières et al, 2012;Nevedal et al, 2020; or formal education (Bussières et al, 2012), CPG quality/conflicting messages (Bussières et al, 2012;Pike et al, 2022), LBP aetiology (Grimshaw et al, 2011)/clinical course (Nevedal et al, 2020;, awareness of LBP assessment/imaging indications , reliance on formal education/ongoing education , purpose of imaging (Bussières et al, 2012;Nevedal et al, 2020), purpose of CPG (Bussières et al, 2012) Social Patient pressure (Blokzijl et al, 2021;Bussières et al, 2012;Nevedal et al, 2020); ability to resist pressure (Blokzijl et al, 2021;Nevedal et al, 2020); patient retaliation (Nevedal et al, 2020).…”
Section: Category Subcategory Influencesmentioning
confidence: 99%